Pathways to Careers in Health Care - King, Christopher T. (W.E. Upjohn Institute, 2019)
This book provides analyses and evaluations of the Health Profession Opportunity Grants (HPOG) program, a federal government demonstration project that is targeted at providing career opportunities in the health care field for individuals in low-wage populations.